Biological characterization of novel Escherichia coli O157:H7 phages and their bacteriostatic effects in milk and pork - Qinghai Ren; Qinghai Ren; Qinghai Ren; Zhiwei Wang; Yichen Ge; Yucui Huang; Wei Zhang; Chunxue Liu; Yubao Li; Shengliang Cao (Frontiers in Microbiology)
Foodborne bacteria, particularly Escherichia coli (E. coli) O157:H7, are significant contributors to foodborne illnesses, with antibiotic overuse exacerbating the issue through the emergence of multidrug-resistant strains. This study investigated the potential of E. coli phages in food safety, examining their biological traits and bacteriostatic properties. Two phages (vB_EcoP_SD2, vB_EcoP_SD6) of E. coli O157:H7 were isolated from slaughterhouse sewage and characterized for morphology, genomic composition, phage phylogenetic tree, optimal multiplicity of infection (MOI), one-step growth curve, thermal and pH stability and antibacterial efficacy. The optimal MOIs of vB_EcoP_SD2 and vB_EcoP_SD6 was 0.1 and 0.01, and temperature range for maintaining activity was 4°C to 55°C. The host range of vB_EcoP_SD2 and vB_EcoP_SD6 was 65% (13/20) and 55% (11/20), which was partially complementary to each other (75%, 15/20). Notably, vB_EcoP_SD2 displayed a latent period of 10 min, a burst period of 80 min, and a burst volume of 80 PFU per cell, while vB_EcoP_SD6 had a burst volume of 10 PFU per cell. Comprehensive whole-genome analysis confirmed two phages has no presence of pathogenic factors or resistance genes. Genomic comparisons suggest vB_EcoP_SD2 and vB_EcoP_SD6, respectively, constituted a novel member of a new genus, Justusliebigvirus genus and Kayfunavirus genus which genome, respectively, was found to be 1,49,066 bp, 40,202 bp long with an average GC content of 37.5 and 49.8%. The phages effectively inhibited host bacteria in LB broth for at least 6 h and showed promise in inhibiting bacteria in milk and pork, which indicated that the two phages exhibited a favorable bacteriostatic effect on milk and pork within the first 6 h under the optimal MOI. In the milk bacteriostasis experiment, vB_EcoP_SD2 could reduce bacteria by 3.16 × 104 CFU/mL, and vB_EcoP_SD6 could reduce bacteria by 1.05 × 104 CFU/mL. Phage vB_EcoP_SD2 decreased bacteria by 1.14 × 104 CFU/mL, and vB_EcoP_SD6 decreased bacteria by 2.04 × 103 CFU/mL in the pork. There was no disparity in bacteriostatic effect of different MOI within the first 6 h, but bacteriostatic effect of all groups still remained different from that of the control group. This study indicates the two phages possess excellent biological characteristics, thereby providing a theoretical foundation for the subsequent development of natural fungicides.